Peran Mediasi Komitmen Organisasi: Kontribusi Karakteristik Individu terhadap Kinerja Pegawai - Ahmad Ahmad (JMK (Jurnal Manajemen dan Kewirausahaan), 2020)
This study aims to explore the contribution effect of individual characteristics on organizational commitment and employee performance. The design of this research is a survey method using a questionnaire. The sampling technique was proportional stratified random. The number of respondents was determined as 125 employees through the table krejcie-morgan of 220 State Civil Servants, obtained 140 units of analysis (State Civil Apparatus at the South Sulawesi Provincial Health Office), only in its implementation there were 15 respondents who gave incomplete responses so that overall only 125 respondents used. The quantitative approach is used to test and prove hypotheses through the use of WarpPLS 6.0. The results of this study indicate that individual characteristics have a significant impact on employee commitment and performance, commitment also shows real results on employee performance. The resulting mediation role test shows that organizational commitment is not stated as a mediator because without the support of organizational commitment, in its implementation individual characteristics are also able to provide tangible results in improving performance.